2014
DOI: 10.5560/znc.2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Investigation of Anticancer, Cell-Cycle-Inhibitory, and Apoptosis-Inducing Effects of Diversin, a Natural Prenylated Coumarin, on Bladder Carcinoma Cells

Abstract: Chemotherapy is one of the main strategies for reducing the rate of cancer progression or, in some cases, curing the tumour. Since a great number of chemotherapeutic agents are cytotoxic compounds, i. e. similarly affect normal and neoplastic cells, application of antitumour drugs is preferred in cancer management and therapy. In this study, the cytotoxicity of diversin was evaluated in 5637 cells, a transitional cell carcinoma (TCC) subline (bladder carcinoma), and normal human fibroblast cells using the 3-(4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It has been reported that scopoletin and its derivatives have lower cytotoxic effects on PBMC than tumor cells (Cai et al, 2013). A prenylated coumarin, diversin, has been observed to exert considerable cytotoxic effects in bladder carcinoma 5637 cells, but not on normal human fibroblast cells (Haghighitalab et al, 2014). In PBMC, only large concentrations of the coumarin compounds elicited a cytostatic action (Lopez-Gonzalez et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that scopoletin and its derivatives have lower cytotoxic effects on PBMC than tumor cells (Cai et al, 2013). A prenylated coumarin, diversin, has been observed to exert considerable cytotoxic effects in bladder carcinoma 5637 cells, but not on normal human fibroblast cells (Haghighitalab et al, 2014). In PBMC, only large concentrations of the coumarin compounds elicited a cytostatic action (Lopez-Gonzalez et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Scopoletin prevented proliferation of human prostate tumor PC3 cells by arresting cell cycle at G0/G1 and S phases (Liu et al, 2001). Diversin was found to produce considerable cytotoxic effects in bladder carcinoma 5637 cells by blocking G2 phase of the cell cycle (Haghighitalab et al, 2014). It has been reported that coumarin and 7-hydroxycoumarin inhibited cell growth by indu- cing cell cycle arrest in the G1 phase in lung carcinoma cell lines (Lopez-Gonzalez et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The anticancer and cytotoxic activities of synthetic and natural coumarins with different functional groups on their basic structure (Figure 2) have been reported by several investigators. These studies showed the anticancer activity of coumarins against breast cancer [89], colon cancer [94], lung cancer [24], ovarian cancer [95], hepatocellular carcinoma [96], bladder carcinoma [97], leukemia [98], and other types of cancer in vitro and in vivo, via different mechanisms, including free-radical scavenging, antioxidant activity [99], induction of cell cycle arrest [100], interaction with various signaling pathways with important role in cell differentiation and proliferation [101], telomerase and carbonic anhydrase inhibition [102,103], and antiangiogenic activity [104]. For example, Taniguchi and co-workers [105] isolated eight coumarins from the leaves of Rhizophora mucronata and reported the anticancer effects of methoxyinophyllum P, calocoumarin B, and calophyllolide against HeLa cells (cervical cancer), with IC 50 equal to 3.8, 29.9, and 36.4 μM, respectively, and HL-60 cells (promyelocytic leukemia cells) with IC 50 of 12.9, 2.6, and 2.2 μM, respectively.…”
Section: Coumarinsmentioning
confidence: 99%
“…The molecular modeling of coumarins and various types of substitutions in their nuclei, represented by benzo-α-pyrone, may open new directions in the search and design of new, more potent compounds as effective adjuvants for the treatment of various diseases [ 35 ]. The interest in coumarins as potential anticancer agents in the treatment of tumors results from both in vitro and in vivo studies reporting that these compounds are effective in preventing the proliferation of bladder cancer [ 36 ], colon cancer [ 37 ], lung cancer [ 38 ], leukemia [ 39 ], and breast cancer [ 40 ] through different mechanisms of action, including cell cycle arrest, modulation of estrogen receptors, inhibition of DNA-associated enzymes such as topoisomerase [ 41 ], inhibition of angiogenesis, several types of heat shock proteins, and activity of enzymes involved in the pathophysiology of cancer, such as telomerase, monocarboxylate transporters, carbonic anhydrase, aromatase, and sulfatase [ 42 ], as well as modulation of different signaling pathways, such as the regulation of mitogen-activated protein kinase expression, signal transducers, and activators of transcription 3, phosphatidylinositol-3-kinase/AKT, and nuclear factor kB [ 43 ]. It is worth noting that some coumarins and their synthetic derivatives have shown promising activity against several types of cancer in clinical trials [ 44 ].…”
Section: Introductionmentioning
confidence: 99%